2001
DOI: 10.1097/00054725-200105000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Supplementation Tightens “Leaky Gut” in Crohn’s Disease

Abstract: Our findings show that zinc supplementation can resolve permeability alterations in patients with Crohn's disease in remission. Improving intestinal barrier function may contribute to reduce the risk of relapse in Crohn's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
114
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(119 citation statements)
references
References 25 publications
(25 reference statements)
2
114
0
3
Order By: Relevance
“…Zinc deficiency is frequently found in IBD patients and linked to attenuated renewal of the epithelium and the onset severe diarrhoea [9][10][11]. Consistently, zinc supplementation to Crohn's disease patients during clinical remission or in animal models of experimental colitis reduced intestinal permeability and mucosal damage [12][13][14][15]. A specific Zn 2þ sensing receptor (ZnR) was functionally described in this tissue [16,17] and was later associated with GPR39 as the molecular moiety mediating its activity [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Zinc deficiency is frequently found in IBD patients and linked to attenuated renewal of the epithelium and the onset severe diarrhoea [9][10][11]. Consistently, zinc supplementation to Crohn's disease patients during clinical remission or in animal models of experimental colitis reduced intestinal permeability and mucosal damage [12][13][14][15]. A specific Zn 2þ sensing receptor (ZnR) was functionally described in this tissue [16,17] and was later associated with GPR39 as the molecular moiety mediating its activity [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Zinc deficiency has been reported in patients with inflammatory bowl disease (Solomons et al, 1977;Hendricks and Walker, 1988), which is associated with increased intestinal permeability. On the other hand, zinc supplementation has been found to preserve intestinal permeability in patients with Crohn's disease (Sturniolo et al, 2001) and in rats with experimental colitis (Sturniolo et al, 2002). Ethanol appears to impair the absorption of zinc from the intestine.…”
Section: Preservation Of Intestinal Epithelial Barrier Functionmentioning
confidence: 99%
“…To test the potential of our analysis in unraveling novel aspects of physiology in healthy and pathological conditions, as well as to link it with the underlying biological effects, we applied the ZNP network/functional analysis to a real case scenario. Zinc was shown to represent a key factor in maintaining the integrity of the intestinal epithelium, both in vitro and in vivo (Iwaya et al 2011;Sturniolo et al 2001Sturniolo et al , 2002. Several lines of evidence suggest that intestinal epithelial cells play a critical role in gut homeostasis in chronic inflammatory bowel disorders such as Crohn's disease (CD) and ulcerative colitis (UC).…”
Section: Topological Analysis Of the Znp Networkmentioning
confidence: 99%
“…It is therefore extremely important to gain further knowledge on the modulatory role of specific nutrients in gut homeostasis, both in healthy and in pathological conditions. Low levels of plasma zinc have frequently been associated with IBD, while zinc supplementation was reported to improve intestinal barrier function in CD patients, as well as in animal models, by contributing to the resolution of alterations in permeability of the gut mucosa and to reducing the risk of relapse (Hering and Schulzke 2009;Matsui 1998;Sturniolo et al 2001Sturniolo et al , 2002. Marginally, zinc-deficient diets were shown to worsen experimentally induced colitis in rats (Iwaya et al 2011), and in vitro evidences have shown that mild zinc deficiency renders intestinal cells susceptible to inflammatory cytokineinduced apoptosis, therefore contributing to epithelial barrier disruption (Ranaldi et al 2013).…”
Section: Introductionmentioning
confidence: 99%